1036 Workers' health and risk for employment injuries – a case control study. (24th April 2018) - Darus, Azlan; Mansor, Ahmad Fuad; Aziz Mohammed, Mohammed Azman
Abstract : Introduction: Risks for occupational accidents may be attributed to the work, worker or the workplace. Numerous studies had identified inherent risk of the workers that exposes them to employment Employees' general health, determined through identifying risk factors of non-communicable diseases is currently an important consideration in workplace safety and health measures. This study seeks to investigate the relationship between employees' general health and risks for employment injuries. Methodology: A case-control study is conducted using a database of employees in Malaysia who underwent a mass general health screening program from the year 2013 to 2016 for social insurance scheme as a sampling frame. Cases were identified from database of employees who were compensated for occupational injury during the same period. Matching controls are selected from the sampling frame based on none-health factors such as geographical location, type of industry and occupation status. General health variable included in the measurements are body mass index, hypertension, diabetes, hypercholesterolaemia, waist circumference and metabolic syndrome. Bivariate analysis and logistic regression are conducted to identify the relationship between health status and employment injury. Results: A total of 4 72 093 employee health screening data were available for analysis. The prevalence of overweight, obesity, hypertension, diabetes and hypercholesterolaemia were 39%, 34%, 27%, 9% and 62% respectively. There were 256, 343 cases of employment injury reported in the social security database within the study period. Initial analysis indicated employment injury to be associated with body mass index and metabolic syndrome. Discussion: Non-communicable diseases are now deemed to be an important threat to employees and businesses alike. The findings of this study is important in building the business case for workplace health promotion activities, as health of the employees may directly affect their safety and health performance, and therefore the performance of the businesses.